Nitrogen Fertilizer Modulates Plant Growth, Chlorophyll Pigments and Enzymatic Activities under Different Irrigation Regimes - Ihsan Muhammad; Li Yang; Shakeel Ahmad; Saqib Farooq; Abdullah Ahmed Al-Ghamdi; Ahmad Khan; Muhammad Zeeshan; Mohamed S. Elshikh; Arshad Mehmood Abbasi; Xun-Bo Zhou (Agronomy, 2022)
Nitrogen fertilization and irrigation patterns have been extensively studied for common maize (Zea mays L.), but there is limited published work for Zhengda 619, especially in subtropical areas. Nitrogen (N) fertilizer and irrigation play an important role in crop growth and yield improvements. The study aimed to investigate the yield, growth, chlorophyll content, reactive oxygen species (ROS) and enzyme activities of hybrid maize (Zhengda 619) under greenhouse conditions. Individual plants grown in plastic pots were subjected to two irrigation types—low irrigation (LW; 60% field capacity) and high irrigation water (HW; 80% field capacity)—and five N rates. Our results demonstrate that the LW irrigation increased dry matter, kernel yield, leaf chlorophyll, total root length, root diameter, root volume, and root surface area, as well as soil enzymes and plant antioxidant enzymes, while it lowered malondialdehyde (MDA), proline, and ROS. Moreover, most of the above parameters increased with increasing N application rates up to N3 under LW irrigation due to the increased N availability to the plant and soil enzymes. It is concluded that increasing N rates could improve soil enzyme activities as well as plant antioxidant enzymes and decrease ROS, ultimately resulting in a higher kernel yield under LW irrigation.